2019
DOI: 10.1371/journal.pone.0226492
|View full text |Cite
|
Sign up to set email alerts
|

An improved understanding of ungulate population dynamics using count data: Insights from western Montana

Abstract: Understanding the dynamics of ungulate populations is critical given their ecological and economic importance. In particular, the ability to evaluate the evidence for potential drivers of variation in population trajectories is important for informed management. However, the use of age ratio data (e.g., juveniles:adult females) as an index of variation in population dynamics is hindered by a lack of statistical power and difficult interpretation. Here, we show that the use of a population model based on count,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 81 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…We found that although elk calf recruitment increased following the mountain lion harvest treatment, the effects of the treatment on recruitment were short-term. Calf recruitment responds to annual variability in winter severity and growing season conditions both in our study area (Paterson et al 2019b) and in general (Garrott et al 2003, Griffin et al 2011, Lukacs et al 2018. However, even after accounting for annual and environmental variation using a population modeling approach, our dataset showed a short-term increase in recruitment following treatment (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We found that although elk calf recruitment increased following the mountain lion harvest treatment, the effects of the treatment on recruitment were short-term. Calf recruitment responds to annual variability in winter severity and growing season conditions both in our study area (Paterson et al 2019b) and in general (Garrott et al 2003, Griffin et al 2011, Lukacs et al 2018. However, even after accounting for annual and environmental variation using a population modeling approach, our dataset showed a short-term increase in recruitment following treatment (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The elk modeling process applied in this study also offers a novel approach that provides advancements and improvements over traditional methods that have been used to interpret monitoring data. The integrated population model allowed for biological inferences that would otherwise have likely been masked by the lack of statistical power induced by not treating observations as a biological process time series and the variance associated with the observation process (Paterson et al 2019 b ). Detecting the effects of carnivore harvest on ungulate populations is difficult (e.g., National Research Council 1997, Hurley et al 2011), and our approach, which accounted for the process and observations separately, allowed for stronger inference regarding these relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWE acc represented the effects of winter severity and was estimated as the mean value of cumulative daily winter snow water equivalent across each population’s winter range (https://www.nohrsc.noaa.gov/). Precipitation and NDVI covariates represented the effects of growing season conditions on forage resources and were estimated during the early (May–June) and late summer (July–September) as the mean value across each population’s summer range (Paterson et al 2019). We evaluated one covariate that indexed population‐level predation risk from mountain lions (LION) using two steps.…”
Section: Methodsmentioning
confidence: 99%
“…gov/). Precipitation and NDVI covariates represented the effects of growing season conditions on forage resources and were estimated during the early (May-June) and late summer (July-September) as the mean value across each population's summer range (Paterson et al 2019). We evaluated one covariate that indexed population-level predation risk from mountain lions (LION) using two steps.…”
Section: Data Collectionmentioning
confidence: 99%